Faktor Pendorong Motivasi Belajar Mahasiswa Politeknik Negeri Sriwijaya - Rita Martini; Sulaiman Muhamad Sulaiman (EKSISTANSI, 2018)
This study aims to analyze the influence of intrinsic and extrinsic factors (lecturer quality, lecture material, lecture methods, lecture rooms, and library facilities) on student motivation both simultaneously and partially. The research population is all students majoring in Polsri Accounting. The sample is determined by simple random sampling. Data collection is done by questionnaire, interview and observation. Data analysis uses path analysis. The results showed the influence of intrinsic factors, lecturer quality, lecture material, lecture methods, lecture rooms, and library facilities on simultaneous student learning motivation is strong and has a positive direction. This indicates an increase in student motivation can be easily achieved if intrinsic factors, the quality of lecturers, materials, methods, lecture rooms, and library facilities are improved simultaneously.